Political Bigotry: An Analysis of Scale Development - Özpolat, Ayşe; Şekerci, Tuba (My University, 2025)
When prejudice or fanaticism is expressed through behavior on the part of a group or society as a whole, it is a sign of underlying conflict. The goal of this study is to create a valid and reliable scale to assess whether bigotry exists based on political institutions. By scanning the literature, a pool of 49 items was created by consulting the opinions of 4 academics, and then an expert evaluation form was given to 11 experts using Davis technique. The draft scale's elements have content validity values ranging from 1 to 0.63. Exploratory factor analysis was used to present the validity of the measure (EFA). The two-factor scale accounts for 63,012 percent of all variance. The scale's initial reliability investigation showed Cronbach Alpha coefficient as 0.937. The sub-dimension for Out-group Aggressive Political Bigotry Behaviors Cronbach Alpha was determined as 0.940; In-Group Favouring Political Bigotry Behaviors was determined as 0.781. As a result of test-retest positive and significant correlation was found between results. The sub-dimension of Out-group Aggressive Political Bigotry Behaviors, which was shown to have highest connection with overall bigotry values (r=,988), and sub-dimension of In-Group Favouring Political Bigotry Behaviors, which had lowest correlation (r=,695), were both bigoted
Keywords: Prejudice; Bigotry; Political Bigotry